Experimental and numerical evaluation of the hygrothermal performance of a hemp lime concrete building: A long term case study. (15th May 2018) - Moujalled, Bassam; Aït Ouméziane, Yacine; Moissette, Sophie; Bart, Marjorie; Lanos, Christophe; Samri, Driss
Abstract: Hemp-lime concrete (HLC) is a bio-based material which is currently undergoing a growing development. HLC is a low embodied energy material and an excellent hygrothermal regulator. Its thermal, hygric and mechanical properties are well known, and its capacity to reduce energy needs and to improve hygrothermal comfort is demonstrated across many laboratory and numerical studies. However, there are few works about its hygrothermal performance in real climatic conditions on the scale of a building. In order to address this issue, a long term in-situ measurement is carried out to analyze the hygrothermal performance of a HLC individual dwelling-house during 4 years. The analysis of the hygrothermal behavior of a wall is achieved by comparing measurements and numerical simulations results. In this study, two simulation tools are used and compared. The first tool is based on the well-known Wufi software. In the second simulation tool, hysteresis phenomenon and temperature-dependence of moisture content are considered in a heat and moisture transfer model. In-situ monitoring of walls temperatures shows the ability of HLC to almost completely dampen variations of external temperature with about 12 h time-shift. The evolution of indoor relative humidity confirms that HLC has an excellent moisture buffer performance. Comparisons between numerical and experimental results highlight the interest to consider the effect of temperature on sorption process in the simulation of the hygrothermal response of a HLC wall in real climatic conditions. Highlights: Hygrothermal performance of a HLC building monitored during 4 years is evaluated. Hysteresis and temperature-dependence of moisture content effects are discussed. HLC helps to maintain a good hygrothermal comfort level in winter and summer. HLC is confirmed to be a good hygrothermal regulator. Effect of temperature on sorption enables more realistic results in simulation